Perbedaan Metode Pengolahan Pascapanen dalam Memengaruhi Kadar Kafein Roasted Bean Kopi Robusta Argopuro: The Differences in Post-Harvest Processing Methods In Affecting Caffeine Content Of Argopuro Roasted Coffee Beans - Annisa Lutfi Alwi; Elok Dara Zulisma; Pascal Ryan Pramudianto; Alfian Juliansyah; M Mikail Rabbani; Putra Prayogo; Luluk Elvi Diana; Anni Nuraisyah; Rizky Nirmala Kusumaningtyas; Descha Giatri Cahyaningrum (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
This study aims to determine the caffeine content of Argopuro Jember robusta coffee beans based on differences in post-harvest processing methods. The research was conducted at the Jember State Polytechnic Agricultural Products Processing (PHP) Laboratory and the Jember State University Integrated Testing Unit Laboratory in June-September 2022. The samples were robusta coffee logs originating from the Argopuro area of ​​Jember. The post-harvest coffee processing process is divided into four (4) methods, namely natural processing (dry process), semi-wet processing, wet (full wash process), and honey processing. Green beans from the results of each processing method are roasted at light, medium, and dark levels. The roasted bean caffeine content test from each post-harvest processing method at each roasting level was carried out descriptively (simple, without repetition). Overall, the caffeine content of the roasted beans produced in this study still meets the SNI 01-3542-2004 standard, a maximum of 2%. The caffeine content of Argopuro Jember robusta coffee roast beans at the light roast level ranges from 1.44-1.65%, 1.38-1.92% for medium roast, and 1.61-1.81% for dark roast. The highest caffeine content in roasted beans at each roasting level is 1.65% (dry process), 1.92% (full wash process), and 1.81% (full wash process), respectively. Meanwhile, roasted beans with the lowest caffeine content with a value of 1.38% are produced using the semi-wet process processing method at a medium roast level. The fluctuations in caffeine values ​​produced in this study indicate that post-harvest processing methods do not affect the caffeine content of roasted beans at light, medium, or dark roast levels.